1999
DOI: 10.1006/dbio.1999.9265
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of SHP-2 and ERK Signalling Promotes Self-Renewal of Mouse Embryonic Stem Cells

Abstract: The propagation of pluripotent mouse embryonic stem (ES) cells depends on signals transduced through the cytokine receptor subunit gp130. Signalling molecules activated downstream of gp130 in ES cells include STAT3, the protein tyrosine phosphatase SHP-2, and the mitogen-activated protein kinases, ERK1 and ERK2. A chimaeric receptor in which tyrosine 118 in the gp130 cytoplasmic domain was mutated did not engage SHP-2 and failed to activate ERKs. However, this receptor did support ES cell self-renewal. In fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
442
2
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(486 citation statements)
references
References 70 publications
29
442
2
7
Order By: Relevance
“…Since gp80 RNA is not expressed in P19 EC cells we conclude that IL-6 does not signal due to the absence of the IL-6 binding receptor. These results are in agreement with previously published data in which addition of the soluble IL-6 receptor was required to initiate IL-6 signal transduction in mouse ES cells [35].…”
Section: Figsupporting
confidence: 94%
See 2 more Smart Citations
“…Since gp80 RNA is not expressed in P19 EC cells we conclude that IL-6 does not signal due to the absence of the IL-6 binding receptor. These results are in agreement with previously published data in which addition of the soluble IL-6 receptor was required to initiate IL-6 signal transduction in mouse ES cells [35].…”
Section: Figsupporting
confidence: 94%
“…In the absence of ERK signaling, a sustained STAT3 activation was observed in response to gp130 receptor activation. It was concluded that ERK activation is not required for self-renewal of mouse ES cells and that the growth of undifferentiated ES cells was even enhanced in the presence of PD98059 [35]. Possibly, the effects of PD98059 on ES growth are not directly related to enhanced activation of STAT3 but rather related to enhanced effects of PD98059 on gene transcription in general, possibly by modulating the activity of the basal RNA polymerase transcription machinery.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Leukemia inhibitory factor (LIF) 2 plays an important role in maintaining self-renewal of murine ES (mES) cells (1,2) via activation of STAT3 (3)(4)(5)(6) and induction of c-Myc (7). LIF also activates additional signals including the Ras/ERK kinase pathway (8,9), ribosomal S 6 kinases (10), phosphoinositide 3-kinases (11), and Src kinases (12). However, whereas LIF-induced STAT3 activation promotes self-renewal, LIF-induced ERK activation appears to promote differentiation (8), leading to the proposal that the balance between STAT3 and ERK signals contributes to the determination of mES cell fate (13).…”
mentioning
confidence: 99%
“…Previous studies suggested that the ERK/mitogenactivated protein kinase (MAPK) pathway plays a negative role in mESC self-renewal [11,52]. Based on this prior knowledge, Ying et al [53] found that application of MAPK/ERK kinase (MEK) and/or fibroblast growth factor (FGF) receptor inhibitors can prevent mESC differentiation under defined conditions without LIF supplementation.…”
Section: Rationale-based Chemical Approachesmentioning
confidence: 99%